Perlindungan Hukum Terhadap Konsumen Pada Perjanjian Pembiayaan dengan Fidusia Tidak Terdaftar - Elis Herlina; Sri Santi (Fakultas Hukum Universitas Islam Indonesia, 2018)
Fiduciary guarantee shall be registered, so that it has execution order, but sometimes fiduciary guarantee is accepted even if it is not registered. The problem in this study was how is the legal protection for consumers in a fiduciary agreement that is made without a notarial deed and is not registered at the Fiduciary Registration Office seen from Law Number 42 of 1999 concerning Fiduciary Guarantee and Law Number 8 of 1999 concerning Consumer Protection. This was a normative legal research. The results of the study concluded that the legal protection of consumers in a financing agreement with an unregistered fiduciary guarantee is that the principal (someone hiring fiduciary agent) can sue for compensation against the fiduciary agent on the basis of unlawful acts as stipulated in Article 1365 of the Civil Code. In addition, in the event of a crime, a person can be sued by Article 368 of the Criminal Code. Financing agreements with fiduciary guarantees shall contain clauses in accordance with the Consumer Protection Law because regarding this violation, business actors are punishable with maximum imprisonment of 5 (five) years or a maximum fine of IDR 2,000,000,000.00.